PERSPECTIVES OF PARENTS ON HOMESCHOOLING IN PAKISTAN: MOTIVATIONS, CHALLENGES AND LONG-TERM IMPACTS - Rehan, Qurratulain; Noreen, Sumaira (Journal of Arts & Social Sciences, 2025)
This qualitative research study focuses on the participation experiences of parents homeschooling in Pakistan, their motivations, challenges faced by them in this process, and management strategies regarding home education. A qualitative research design was used, and the data were gathered using semi-structured interviews with ten homeschooling parents selected through purposive sampling (to fit with different perspectives). Thematic analysis was utilized to find general patterns across homeschooling experiences following Braun and Clarke’s (2006) framework. The data revealed three types of engaging with homeschooling based on how long they had been homeschooling: The Newcomer, The Average Joe, and The Lifers, showing the sense of growing confidence and strategies that new families feel as they get going. The research also highlighted three significant barriers: social isolation, availability of quality education and extracurricular activities, and time/resource management. Even with these challenges, homeschooling parents said it had benefits like individualized education, flexibility and strong parent-child connections. During this time, digital solutions, like YouTube, Khan Academy and other online learning platforms were necessary to assist learning and fill the gap, though worries about screen time excess and reliance on technology were also raised. This research contributes to literature on the important role of home educating attendees in reconciling their understanding of home education with the need for equitable opportunities for those families who do wish to home educate. Following studies should investigate the academic, social and career successes of homeschooled children, to make sure that they are actually able to transition into higher education and the working world smoothly.